2017
DOI: 10.1002/ptr.5846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tilianin on Proliferation, Migration and TGF-β/Smad Signaling in Rat Vascular Smooth Muscle Cells Induced with Angiotensin II

Abstract: Flavonoid Tilianin was isolated from Dracocephalum moldavica, and its pharmacological mechanism on proliferation, migration and the TGF-β/Smad signaling pathway in rat vascular smooth muscle cells (VSMCs) induced with Angiotensin II (Ang II) was systematically evaluated. Primary rat VSMCs were stimulated with Ang II to induce proliferation. The cells were then treated with Tilianin for 24 or 48 h. MTT assay and Transwell assays were used to evaluate the effects of Tilianin on proliferation and migration. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Some of the vascular lesions, such as atherosclerosis of blood vessels, are considered to be risk factors in the process of cognitive impairment, among which endothelial dysfunction causes aberrant proliferation and migration of the adjacent VSMCs, resulting in vascular function and structure changes, eventually leading to cognitive impairment in VaD [ 32 ]. Our previous studies have illustrated that tilianin inhibits the proliferation and migration of rat VSMCs via suppressing the TGF- β /Smad pathway, thereby improving vascular function against atherosclerosis [ 12 , 13 ]. These previous findings have provided evidence for the cardiovascular protective effects of tilianin that contribute to the potential benefit against VaD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the vascular lesions, such as atherosclerosis of blood vessels, are considered to be risk factors in the process of cognitive impairment, among which endothelial dysfunction causes aberrant proliferation and migration of the adjacent VSMCs, resulting in vascular function and structure changes, eventually leading to cognitive impairment in VaD [ 32 ]. Our previous studies have illustrated that tilianin inhibits the proliferation and migration of rat VSMCs via suppressing the TGF- β /Smad pathway, thereby improving vascular function against atherosclerosis [ 12 , 13 ]. These previous findings have provided evidence for the cardiovascular protective effects of tilianin that contribute to the potential benefit against VaD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that tilianin displays cardiovascular protection; inhibits atherosclerosis, hypertension, diabetes, inflammation, and depression; and is an antioxidant, among its other properties [ 9 11 ]. As one of our ongoing studies, tilianin exerts beneficial effects on alleviating atherosclerosis lesions in vascular smooth muscle cells through inhibition of the TGF- β /Smad signaling, illustrating the potential protective effects of tilianin on vascular dysfunction [ 12 , 13 ]. Furthermore, tilianin has been shown to protect the brain tissue of rats against acute cerebral ischemia-reperfusion [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…cDNA was amplified with specific primers predesigned from Kumei (Jilin, China). Real‐time PCR (Cao et al, ) was performed using the following conditions: 95°C for 10 min and 40 cycles of 95°C for 15 s, 60°C for 30 s, and 95°C for 15 s. A final dissolution curve from 60°C to 95°C, with a 0.3°C increase per second, was generated for real‐time monitoring of fluorescence intensity changes. The cell primer sequences used for each of the related genes are as follows: vimentin, sense AGTCCACTGAGTACCGGAGAC, and antisense CATTTCACGCATCTGGCGTTC; smad3, sense CGTGCGGCTCTACTACAT, and antisense CATCCTGGTGGGATCTTG; smad2, sense CCGACACACCGAGATCCTAAC, and antisense GAGGTGGCGTTTCTGGAATATAA; E‐cadherin, sense ATTTTTCCCTCGACACCCGAT, and antisense TCCCAGGCGTAGACCAAGA; TGF‐β, sense CTGGCGATACCTCAGCAACC, and antisense CTAAGGCGAAAGCCCTCAAT; β‐actin, sense AAGAGCTACGGGCTGCCTGA, and antisense AGCACTGTGTTGGCGTACAG.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was amplified with specific primers predesigned from Kumei (Jilin, China). Real-time PCR (Cao et al, 2017) was performed using the following conditions: 95°C for 10 min and 2.8 | Western blot and enzyme-linked immunosorbent assay BEAS-2B cells and mouse lung tissues were processed with a total protein extraction kit, and the protein samples were stored at 4°C for short-term storage and −80°C for long-term storage. The protein concentration was determined by the BCA method.…”
Section: Real-time Polymerase Chain Reaction Analysismentioning
confidence: 99%
“…В последние годы взгляды на РААС как на классическую вазорегулирующую систему в корне изменились. Многочисленные экспериментальные работы показывают, что отдельные ее компоненты проявляют цитокиноподобные свойства и участвуют в таких процессах, как пролиферация и дифференцировка клеток [14][15][16], синтез внеклеточного матрикса и протеолитических ферментов [16][17][18], генерация кислородных радикалов [19][20][21], выброс цитокинов, хемокинов и белков острой фазы воспаления [22][23][24], экспрессия молекул клеточной адгезии [20,25] и т. д. Кроме того, сегодня дисрегуляция РААС ассоциируется с различными патологиями. Известно, что она задействована в патогенезе таких заболеваний, как артериальная гипертензия (АГ) [26], атеросклероз [27,28], рак [29,30], СД [31,32] и ХПН [33], причем некоторые из этих состояний тесно связаны с процессами, лежащими в основе патофизиологии КАС.…”
Section: обзоры §unclassified